(untitled) (Global Conference on Medical and Health Sciences, 2026)
Understanding brain connectivity has become a central focus in modern neuroscience, particularly in the context of neurological disorders. Functional magnetic resonance imaging (fMRI) provides a powerful, non-invasive method for investigating brain activity and functional connectivity by measuring blood oxygen level–dependent (BOLD) signals. Advances in connectivity analysis have enabled the identification of large-scale brain networks, offering new insights into the neural mechanisms underlying cognition and disease.